Assessment of the Urinary Microbiota of MSM Using Urine Culturomics Reveals a Diverse Microbial Environment - Sawhney, Sanjam S; Johnson, Caitlin; Shupe, Angela; Fine, Jeremy; Dantas, Gautam; Burnham, Carey-Ann D; Yarbrough, Melanie L (Clinical chemistry (Baltimore, Md.), 2022)
Abstract Background The urinary tract is not sterile and is populated by microbial communities that influence urinary health. Men who have sex with men (MSM) are understudied yet have increased risk factors for genitourinary infections. Our objective was to interrogate the composition of MSM urinary microbiota. Methods Midstream urine specimens (n = 129) were collected from MSM (n = 63) and men seen for routine care (clinical cohort, n = 30). Demographics and sexual/medical history were documented. Specimens underwent culture using standard-of-care and enhanced methods designed to isolate fastidious and anaerobic microorganisms. Isolates were identified by MALDI-TOF mass spectrometry or 16S rRNA gene sequencing. Results The MSM cohort was younger (mean (SD), 35.4 (11.26) years) compared to the clinical cohort (62.7 (15.95) years). Organism recovery was significantly increased using enhanced vs standard culture for the MSM (mean of 9.1 vs 0.6 species/sample [P < 0.001]) and clinical (7.8 vs 0.9 species/sample [P < 0.001]) cohorts. The microbial composition of MSM urine specimens was dominated by Gram-positive and anaerobic microbes and clustered distinctly from that of clinical urine specimens. Composition of microbial species recovered within the same subject was dynamic between urine specimens but more similar relative to inter-individual comparisons. Principal coordinate analysis showed no correlation between urinary microbiota composition and age, recent antibiotic use, sexually transmitted infection/HIV status, or sexual practices. Conclusions Enhanced culture recovered a large diversity of microbial species from MSM urine specimens, especially taxa typically associated with mucosal surfaces. These findings may increase understanding of urologic disease in MSM and improve diagnostic methods for detection of genitourinary infections.